PROFIL KERACUNAN PADA ANAK DI INSTALASI GAWAT DARURAT RUMAH SAKIT TERSIER YOGYAKARTA - Ndaru Setyaningrum; Suci Febriani (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2020)
This research was conducted to determine the profile of poisoning in children in the emergency department of Yogyakarta city tertiary hospital. The study was conducted retrospectively by taking data based on the medical records of children in 2016 - 2017. The research subjects were children with an age limit under 12 years. Total cases of poisoning in children in the emergency department of Yogyakarta City tertiary hospital in 2016 were 8 cases and in 2017 there were 11 cases. Most cases of poisoning occurred in 13 boys (68.4%) with an age range of 6 - 12 years 9 (47.4%). Poisoning cases occur predominantly in children who have not attended school 14 (73.7%). The cause of poisoning was successively due to animal bites of 11 cases (57.9%); drug 4 (21%); pesticide 2 (10.5%); food and household products - 1 case each (5.3%). The use of antidotes in this study was for 6 cases (31.6%). The profile of poisoning in children in the emergency department of a tertiary hospital in Yogyakarta is predominantly male (68.4%) with an age range of 6-12 years (47.4%) and not yet educated (73.7%). The dominant cause of poisoning is animal bites (57.9%) and drugs (21%).